Epidemic obesity in the United States: are fast foods and television viewing contributing? - Jeffery, R W (1998)
OBJECTIVES: This study examined the association between TV viewing, fast food eating, and body mass index. METHODS: Associations between hours of TV viewing, frequency of eating at fast food restaurants, body mass index, and behaviors were assessed cross sectionally and longitudinally over 1 year in 1059 men and women. RESULTS: Fast food meals and TV viewing hours were positively associated with energy intake and body mass index in women but not in men. TV viewing predicted weight gain in high-income women. CONCLUSIONS: Secular increases in fast food availability and access to televised entertainment may contribute to increasing obesity rates in the United States.